Effect of the Change of Deposition Time on the Secondary Direction and Abnormal Shape of Grains Growth of SnO2 Thin Films - Jin Jeong (Advances in Materials Science and Engineering)
SnO2 thin films were grown on Si substrate using the low pressure chemical vapor deposition method. Observations made through electron microscopy indicate that thin films tend to grow with a constant direction when deposited at a temperature of 420°C for 5, 10, 20, or 30 min. However, when the deposition time increases, the particles forming the thin films are subject to a secondary growth. Observations made under a high-resolution transmission electron microscope reveal the lattice shape characteristic of thin films, with an overlapped or wrinkled flower form, and indicate that thin films growth takes place in different directions during the secondary growth. Measurements of the Hall effect show that the carriers mobility in the thin films increases linearly with the deposition time, whereas the carrier density decreases. The Hall Rh value increased linearly until 20 min deposition time, whereas for thin film grown for 30 min it decreased rapidly, showing a relatively similar behaviour to the carrier density. This is because as the deposition time becomes longer, the second growth and atypical shape occurs, leading to an increase of the thin films Rh value. This phenomenon indicates that the deposition time of thin films affects their carrier density and atypical overlapped or wrinkled flower form.